BERNOSTALGIA BERSAMA MI BURUNG DARA DENGAN VISITOR CENTER BERGAYA EKLEKTIK - Amanda Christabel; Astrid Kusumowidagdo; Stephanus Evert Indrawan (Universitas Ciputra Surabaya, 2016)
Competition among companies to increase sale is getting fiercer, so branding is on to the public to socialize company image, impression or identity of is necessary. PT. Surya Pratista Hutama is a noodle company which is currently developing the brand of their noodle product. To develop the brand of the company, there should be a forum for public interest and positive responses. Therefore, the company plans to construct a Visitor Center as a space for cooking classes, presentations, and seminars on Mi Burung Dara. The building will be divided into two sections, which are cafeteria on the first floor and mini conference room on the second floor. The concept of the interior design of the building is international taste. To reflect the concept in the building interior, eclectic style, which is a combination of design styles from several periods and locations, is applied. The application of the eclectic style uses several national and international cultures in the building interior.